2023
DOI: 10.1093/g3journal/jkad045
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal deep learning methods enhance genomic prediction of wheat breeding

Abstract: While several statistical machine learning methods have been developed and studied for assessing the genomic prediction (GP) accuracy of unobserved phenotypes in plant breeding research, few methods have linked genomics and phenomics (imaging). Deep learning (DL) neural networks have been developed to increase the GP accuracy of unobserved phenotypes while simultaneously accounting for the complexity of genotype × environment interaction (GE); however, unlike conventional GP models, DL has not been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Yield was measured in all environments, while Germination, Heading, Height and Maturity were determined in three out of four (B5IR, B2IR, and BDRT). Recently this data set was employed by Montesinos-López et al. (2023) for assessing the benefit of applying sparse phenotype field trials for genomic prediction at early testing generation of the population improvement (occurring at F 4 or F 5 )>.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yield was measured in all environments, while Germination, Heading, Height and Maturity were determined in three out of four (B5IR, B2IR, and BDRT). Recently this data set was employed by Montesinos-López et al. (2023) for assessing the benefit of applying sparse phenotype field trials for genomic prediction at early testing generation of the population improvement (occurring at F 4 or F 5 )>.…”
Section: Methodsmentioning
confidence: 99%
“…(2023) . In wheat genomic prediction, multi-modal deep learning models have been explored and applied as a promising approach ( Kick et al., 2023 ; Montesinos-López et al., 2023 ). These studies have demonstrated the potential of multi-modal deep learning in enhancing the accuracy of genomic prediction for wheat traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining physiological and statistical models into a single model has also been explored but not yet widely implemented (Messina et al 2018;Diepenbrock et al 2021;Shahhosseini et al 2021a). Among models with substantial environmental, as well as genetic, components, Best Linear Unbiased Predictor models (BLUPs) and deep neural networks (DNNs) have both been shown to perform well under some scenarios (Washburn et al 2021) with a potential tradeoff in average model performance favoring BLUPs and model consistency across replicates in some cases favoring DNNs (Kick et al 2023) in addition to the ability to more directly incorporate multimodal data (Montesinos-López et al 2023). For most breeding applications however, BLUP models with limited or no environmental data are still considered the gold standard with their relative simplicity, when compared to machine learning, deep learning, and other approaches being a major benefit (Ma et al 2018;Montesinos-López et al 2018;Abdollahi-Arpanahi et al 2020;Nazzicari and Biscarini 2022;Gianola et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of genomic and environmental effects (both those within a farmer's control, i.e., management, and those external to it) are necessary because gene by environmental effects can in some cases exceed purely genetic effects . Furthermore, inclusion of these interactions can improve the predictive accuracy for new environments or cultivars (Li et al 2021;Jarquin et al 2021;Montesinos-López et al 2023).…”
Section: Introductionmentioning
confidence: 99%